2006
DOI: 10.2460/javma.229.6.949
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of dietary modification for treatment of spontaneous chronic kidney disease in cats

Abstract: Objective-To determine whether a renal diet modified in protein, phosphorus, sodium, and lipid content was superior to an adult maintenance diet in minimizing uremic episodes and mortality rate in cats with stage 2 or 3 chronic kidney disease (CKD). Design-Double-masked, randomized, controlled clinical trial. Animals-45 client-owned cats with spontaneous stage 2 or 3 CKD. Procedures-Cats were randomly assigned to an adult maintenance diet (n = 23 cats) or a renal diet (22) and evaluated trimonthly for up to 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
149
0
18

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(181 citation statements)
references
References 15 publications
6
149
0
18
Order By: Relevance
“…[115][116][117] Perhaps the most convincing evidence that there is likely to be a role for phosphorus homeostasis in the progression of CKD comes from the studies that have demonstrated improved survival in those cats that are fed a phosphate restricted diet with evidence of modulation of these important regulatory hormones. 114,190,191 …”
Section: Hyperphosphatemiamentioning
confidence: 99%
“…[115][116][117] Perhaps the most convincing evidence that there is likely to be a role for phosphorus homeostasis in the progression of CKD comes from the studies that have demonstrated improved survival in those cats that are fed a phosphate restricted diet with evidence of modulation of these important regulatory hormones. 114,190,191 …”
Section: Hyperphosphatemiamentioning
confidence: 99%
“…Protein restriction is a common dietary modification in therapeutic RDs,22, 23, 24, 25 and can reduce proteinuria in dogs with glomerulopathies 20. However, if protein restriction is too severe (1.83 g of protein/100 kcal of digestible energy), protein malnutrition can occur 20.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to maintenance diets (MDs), therapeutic RDs may be modified in some or all of the following ways: reducing protein, phosphorus, and sodium content; increasing B‐vitamin content, caloric density, and soluble fiber; a neutral effect on acid‐base balance; supplementing with omega‐3 PUFAs and potassium (feline diets); and adding antioxidants 22, 23. These diets reduce the incidence of uremic crisis and mortality in dogs and cats with azotemic CKD compared with MDs 24, 25. Although RDs have been used in the management dogs with proteinuria,13, 19, 20 their possible benefits in the control of proteinuria in non‐azotemic dogs are unknown.…”
mentioning
confidence: 99%
“…Είναι γενικά παραδεκτό ότι τον ακρογωνιαίο λί θο στην αντιμετώπιση της ΧΝΑ αποτελεί η λήψη ειδι κών διαιτητικών μέτρων (Adams et al 1993, Elliott et al 2000, Elliott 2006, Ross et al 2006a, Ross et al 2006b, Plotnick 2007, αν και ορισμένες σχετικές με λέτες καταλήγουν σε αντιφατικά αποτελέσματα (Adams et al 1994, Fineo et al 1998. Η μειωμένη πε ριεκτικότητα της τροφής σε πρωτεΐνες που πρέπει να έχουν υψηλή βιολογική αξία αποτελεί τον κΰριο στόχο της διαιτητικής αγωγής (Adams et al 1993, Elliott et al 2000, Polzin et al 2000, Elliott 2006, Ross et al 2006a, Plotnick 2007.…”
Section: θεραπειαunclassified
“…Λέξεις ευρετηρίασης: χρόνια νεφρική ανεπάρκεια, σταδιοποίηση, θεραπεία, γάτα ΕΙΣΑΓΩΓΗ Η χρόνια νεφρική ανεπάρκεια (ΧΝΑ) της γάτας προσβάλλει κυρίως μεσήλικα και υπερήλικα ζώα και χαρακτηρίζεται από μη αναστρέψιμες βλάβες στους νεφρούς, με επακόλουθο την αδυναμία τους να απεκκρίνουν τα κατάλοιπα του μεταβολισμού, να εκ κρίνουν και να ανταποκρίνονται στη δράση διαφόρων ορμονών, καθώς και να ρυθμίζουν το ισοζύγιο του νε ροΰ, τη συγκέντρωση ορισμένων ηλεκτρολυτών και την οξεοβασική ισορροπία (Lees 2004, Ross et al 2006a, Ross et al 2006b, Glassock 2008. Για την πρό κληση της ενοχοποιούνται διάφορες αιτίες, αν και στα περισσότερα περιστατικά η αιτιολογία της παραμένει αδιευκρίνιστη (Sturgess 2003, Ross et al 2006a.…”
unclassified